Application of geoinformation systems in the arrangement of public services and amenities of the territorial community - Naradovyi, B. (Land Management, Cadastre and Land Monitoring, 2023)
It has been proved that the geoinformation system of a territorial community is an innovative electronic cartographic resource aimed at the maintenance of the targeted and comfortable community assets management, mainly, the natural, water, forest, mineral, and land resources, engineering, and transport, social, tourist infrastructure, the investment potential of a community providing for the operative communication between the residents and administration of a community. The objective of the Research is to display the amenities of the Lviv Territorial Community according to their function based on their rational application and protection considering the local Building Rules with the implementation of Geoinformation Software QGIS. With the help of the application of the plug-in QuickOSM it displays the vector data of the amenities within Lviv Territorial Community, mainly, the keys “landuse recreation”, “landuse landfill”, “leisure park’, “leisure garden”, “water”, “highway”, and “waterway”. The feasibility of QGIS application for the vector display of amenities within Lviv Territorial Community is presented that shows the advantages of visualization, quick access, administration, and actualization based on the open resources of access to the cartographic materials of the geoportal of Lviv that provides for convenient maintenance of the cartographic database and inventory of the utility system, accounting, and operative inventory of the municipal property objects.